Analytical method validation and determination of dexamethasone in divided powder using reverse phase HPLC - Riswanto, Florentinus Dika Octa; Virginia, Dita Maria; Putri, Dina Christin Ayuning; Yuliani, Sri Hartati (Pharmaciana, 2017)
Dexamethasone as glucocorticoids has been widely used to reduce inflammation and tissue damage in a variety of conditions. It was commonly prescribed in combination with the other compounds such as chlorpheniramine maleate for the relief of asthma. It was important to observe the quality and safety of the combination dosage form, called pulveres or puyer in order to serve the patient oriented medication. This research aimed to develop analytical method validation and determine the content uniformity of the divided powder containing dexamethasone compounded by pharmacy in Yogyakarta and hospital in Central Java, Indonesia. A validated high performance liquid chromatography (HPLC) method was chosen to determine dexamethasone in the samples. The column of ACE 5 C18 (250 x 4.6 mm) was used in this research and the methanol:water (65:35) was used as the mobile phase at the flow rate of 1 mL/min. The UV detection was performed at 239 nm. Analytical method validation was performed on the parameters of system suitability, limit of detection, limit of quantification, accuracy, precision, and linearity. The results showed that dexamethasone contains in divided powder compounded by pharmacy in Yogyakarta and hospital in Central Java were met the acceptance requirement.Â Â